2021
DOI: 10.7554/elife.69795
|View full text |Cite
|
Sign up to set email alerts
|

A zebrafish screen reveals Renin-angiotensin system inhibitors as neuroprotective via mitochondrial restoration in dopamine neurons

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disorder without effective disease-modifying therapeutics. Here, we establish a chemogenetic dopamine (DA) neuron ablation model in larval zebrafish with mitochondrial dysfunction and robustness suitable for high-content screening. We use this system to conduct an in vivo DA neuron imaging-based chemical screen and identify the Renin-Angiotensin-Aldosterone System (RAAS) inhibitors as significantly neuroprotective. Knockdown of the angiotensin receptor 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 80 publications
1
23
0
Order By: Relevance
“…Furthermore, an intracellular RAS was identified in mitochondria and nuclei of dopaminergic neurons, including other RAS components such as AGTR2 and MAS receptors that may counteract the deleterious effects of AGTR1 activation 4 . Recent clinical studies also support a neuroprotective effect of AGTR1 inhibitors 3,5 . The findings of Kamath et al 1 further encourage the development of prodromal clinical trials for angiotensin receptor blockers (ARBS) that can cross the blood‐brain barrier or for molecules inhibiting AGTR1 effects, including those acting on RAS regulatory components (AGTR2, MAS) that counteract AGTR1 activation.…”
mentioning
confidence: 97%
“…Furthermore, an intracellular RAS was identified in mitochondria and nuclei of dopaminergic neurons, including other RAS components such as AGTR2 and MAS receptors that may counteract the deleterious effects of AGTR1 activation 4 . Recent clinical studies also support a neuroprotective effect of AGTR1 inhibitors 3,5 . The findings of Kamath et al 1 further encourage the development of prodromal clinical trials for angiotensin receptor blockers (ARBS) that can cross the blood‐brain barrier or for molecules inhibiting AGTR1 effects, including those acting on RAS regulatory components (AGTR2, MAS) that counteract AGTR1 activation.…”
mentioning
confidence: 97%
“…Finally, our assay could also be valuable to develop biomedical models reproducing human nervous system alterations quantitatively assess the link between axonal transport impairment and disease outcome. In particular, it would be interesting to reproduce our experiments in Zf larvae infected by neurotropic viruses, [47][48][49] in transgenic lines used as models of neurodegenerative diseases, [50][51][52] or upon axonal photoablation 53 to precisely measure the axonal transport impairments in these situations. In case of detection of a significant impairment of axonal transport, our assay could be harnessed to screen therapeutic compounds able to rescue the defect.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we developed a high throughput DA neuron imaging method (Liu et al, 2016) and reported the identification of renin-angiotensin-aldosterone system (RAAS) inhibition as neuroprotective via mitochondrial targeting in DA neurons (Kim et al, 2021). In this study, we present for the first time the results of the entire 1403 HTS bioactive compound screen and uncover additional neuroprotective candidates after secondary validation.…”
Section: Introductionmentioning
confidence: 97%
“…While current therapeutic drug discovery is largely targetbased, the implementation of phenotypic drug discovery has significant advantages particularly for neurodegenerative diseases (Ibhazehiebo et al, 2018;Lam and Peterson, 2019;Kim et al, 2021;Zhang et al, 2021). Phenotypic assays for a direct impact on neuronal integrity can bypass the need to fully understand complex biological processes underlying neurodegeneration, and in many cases provide leads to novel targets (Liu et al, 2016;Moffat et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation